Flow diversion for unruptured fusiform aneurysms of the proximal middle cerebral artery - Gai, Yanting; Nuerdong, Maimaitiali; Jiang, Yicheng; Wang, Wei; Pu, Benfang; Xu, Feng; Song, Donglei (Frontiers in Neurology, 2023)
Background Managing fusiform aneurysms of the proximal (M1) segment of the middle cerebral artery (MCA) is challenging due to difficulties in both surgical and endovascular treatment. In this study, we present our experience using flow diverter stents for managing unruptured M1 segment fusiform aneurysms. Methods We conducted a retrospective review of the database of our institution to identify all patients who underwent flow diversion treatment for unruptured M1 segment fusiform aneurysms. We collected data on patient demographics, aneurysm characteristics, complications, angiographic follow-up results, and clinical outcomes. Results A total of 10 patients (five male and five female patients) with 10 unruptured M1 segment fusiform aneurysms were included in the study. The average age of the patients was 48 years (range: 16–64 years); five patients had aneurysms smaller than 10 mm, four had aneurysms measuring between 10 and 25 mm, and one patient had an aneurysm larger than 25 mm. The successful deployment of flow-diverting stents was achieved in all cases. Procedure-related morbidity was observed in 10% of patients, but there were no deaths. All patients showed good outcomes (modified Rankin Scale score of 0–1); eight out of 10 patients had available follow-up angiography results with a mean follow-up period of 11.6 months (range: 6–24 months). Complete occlusion occurred in six out of eight reviewed cases (75%). Conclusion Our preliminary findings suggest that using flow diversion for treating unruptured fusiform aneurysms in the proximal MCA is feasible and safe, with a satisfactory rate of complete occlusion. However, further studies involving larger case series are needed to validate the durability and efficacy of this treatment approach.